Spiritual and Material Rewards on the Christian-Muslim Frontier: Norman Crusaders in the Valley of the Ebro in the First Half of the Twelfth Century - Villegas-Aristizábal, Lucas (Medievalismo, 2017)
This article explores the involvement of the Norman nobility in the wars between Christians and Muslims in the Ebro Valley in the first half of the 12th Century. The work recognises how the participation of the this particular ethno-cultural group in the peninsula was renovated to a certain degree by the deeds and religious transformation that took place as result of the preaching and success of the crusade. Furthermore, by exploring the careers of Rotrou of Perche, Robert Burdet and Walter Guidvilla this piece demonstrates how their religiosity as well as the filial relations and traditional desire for wealth that characterise this group of warriors, made the Iberian theatre of conflict so attractive at this particular period. Also, this article, tries to show how their Iberians lay and clerical coreligionists perceived the usefulness of these Norman contingents in their conflict with the Almoravids.